PERBEDAAN BERBAGAI KONSENTRASI EKSTRAK GETAH DAUN TANAMAN JARAK PAGAR (JATROPHA CURCUS L.) TERHADAP DAYA HAMBAT BAKTERI STREPTOCOCCUS MUTANS - Saptiwi, Betty (IDENTIFIKASI, 2020)
The purpose of this research is to utilize the potential of Indonesia's natural resources that have not been optimally processed and to produce an alternative toothache medicine that is cheap, easy to use and safe. The benefits are that it can add value to the potential of Indonesia's natural resources and can add to alternative toothache medicines from Indonesia's natural resources. The research consisted of two stages, namely the first stage was the standardization test of the extract of the jatropha leaves (Jatropha Curcus L) and the second stage was the measurement of bacterial inhibition using the first stage extract. The results showed that the extract of jatropha leaves (Jatropha Curcus L) did not show inhibition of the growth of Streptococcus mutans bacteria.